Sticky Polyelectrolyte Shield for Enhancing Biological Half-Life of Growth Factors - Kim, Young; Jeon, Sungmi; Kim, Byulhana; Jeong, Yu Jin; Kim, Tae Hee; Jeong, Subin; Kim, Iljin; Oh, Joomin; Jung, Youngmee; Lee, Kangwon; Choy, Young Bin; Kim, Sang Wha; et al. (American Chemical Society, 2025)
Delivery of secretomes, which includes growth factors, cytokines, and mRNA, is critical in regenerative medicine for cell-to-cell communication. However, the harsh in vivo environment presents significant challenges for secretome delivery. Proteolytic enzymes shorten secretomes' half-lives, and secretomes tend to rapidly diffuse at defect sites. Therefore, a delivery system that ensures prolonged retention and enhanced therapeutic efficacy of secretomes is required. In this study, a Coating Optimized Drug Delivery Enhancement (COD2E) system, a coacervate composed of dopamine functionalized fucoidan and poly-l-lysine, was fabricated for secretome delivery. The dopamine modification significantly enhanced adhesive strength (>7-fold) compared to that of the neat coacervates, which enabled rapid (5 min) and uniform coating ability on collagen sponges. The COD2E system was able to encapsulate fibroblast growth factor (FGF2) and prolong the half-life of FGF2. Notably, its efficacy, demonstrated through a single application of FGF2 encapsulated COD2E on collagen sponge, in a wound model demonstrated a successful tissue repair. The COD2E system is an effective growth factor delivery vehicle since it can protect growth factors, has an antioxidant ability, adheres on various material surfaces, and is hemocompatible.